Septal cholinergic neuromodulation tunes the astrocyte-dependent gating of hippocampal NMDA receptors to wakefulness - Papouin, Thomas (Neuron, 2017)
The activation of the N-methyl D-aspartate receptor (NMDAR) is controlled by a glutamate-binding site and a distinct, independently regulated, co-agonist-binding site. In most brain regions, the NMDAR co-agonist is the astrocyte-derived gliotransmitter D-serine. We found that D-serine levels oscillate in mouse hippocampus as a function of wakefulness, in vitro and in vivo. This causes a full saturation of the NMDAR co-agonist site in the dark (active)-phase that dissipates to sub-saturating levels during the light (sleep)-phase, and influences learning performance throughout the day. We demonstrate that hippocampal astrocytes sense the wakefulness-dependent activity of septal cholinergic fibers through the α7-nicotinic acetylcholine receptor (α7nAChR), whose activation drives D-serine release. We conclude that astrocytes tune the gating of synaptic NMDARs to the vigilance state and demonstrate that this is directly relevant to schizophrenia, a disorder characterized by NMDAR and cholinergic hypofunctions. Indeed, bypassing cholinergic activity with a clinically-tested α7nAChR agonist successfully enhances NMDARs activation.